2022
DOI: 10.3389/fpls.2022.1075407
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged drought regulates the silage quality of maize (Zea mays L.): Alterations in fermentation microecology

Abstract: Prolonged drought stress caused by global warming poses a tremendous challenge to silage production of maize. Drought during maize growth and development resulted in altered micro-environment for silage fermentation. How fermentation of silage maize responds to moisture scales remains uncharted territory. In this research, Maize water control trials were conducted and the silage quality and microbial community of drought-affected maize were determined. The results showed that drought stress significantly reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
3
1
Order By: Relevance
“…This finding agrees with that of Koua et al (2021) on the reduction of neutral detergent fiber (NDF) by drought stress following one generation of exposure. However, whereas Zi et al (2022) found no significant difference in NDF levels between groups in maize due to somatic memory, we found higher NDF levels in wheat seeds due to transgenerational and intergenerational memories.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding agrees with that of Koua et al (2021) on the reduction of neutral detergent fiber (NDF) by drought stress following one generation of exposure. However, whereas Zi et al (2022) found no significant difference in NDF levels between groups in maize due to somatic memory, we found higher NDF levels in wheat seeds due to transgenerational and intergenerational memories.…”
Section: Discussioncontrasting
confidence: 99%
“…The exogenous fibrotic enzyme treatment groups significantly reduced the pH of the silage and increased the content of lactic acid, acetic acid, and LAB. This may be due to the fact that both cellulase and xylanase treatments reduced the cellulose and hemicellulose content in the oat cell wall of the silage, providing sufficient fermentation substrates for LAB [ 28 ]. Different silage times did not affect the butyric acid content in silage, but exogenous fibrotic enzyme treatment reduced the generation of butyric acid content, which may be due to the inhibition of Clostridium butyricum growth by other dominant microorganisms with higher abundance [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, cellulase treatment did not increase the WSC content, which may be due to the fact that the pH in silage did not drop below 4.2, causing other harmful microorganisms to continue using sugar [14]. The ether extract significantly increased in the late stage of silage, which is due to fermentation that can be attributed to the breakdown of the cell walls of the forage material and the release of lipids from intracellular organelles and membranes; the microbes involved in the fermentation process also contribute to this increase as they help to break down the plant material and release more lipids [31].…”
Section: Materials Characteristics and Silage Qualitymentioning
confidence: 99%